Few effects of sow lactational stress on maternal behavior, but altered physiology with implications for piglet early-life stress coping - Jørgensen, Cathinka C.; Gimsa, Ulrike; Moscovice, Liza R. (Applied animal behaviour science, 2025)
Sows in conventional livestock farming are subject to several challenges, many of which are associated with suboptimal housing conditions. These conditions increase the risk of maternal stress during the lactational period, which can cause changes in maternal care with subsequent influences on piglet early life experiences. We aimed to investigate how maternal stress during lactation influences maternal care, by analyzing changes in sow behaviors, including aggression, nursing events and social contact with offspring, and physiology, focusing on hormones important for stress regulation (cortisol, CORT) and social bonding (oxytocin, OXT). We also wanted to assess how two different rearing environments would influence offspring early life behavioral and physiological responses during a maternal separation. In addition, piglets were separated with or without littermates present, to examine effects of social buffering on piglet responses. From lactation day 2–15, sows were treated with an injection of adrenocorticotropic hormone (ACTH; n = 10) or a saline solution (C; n = 10), to simulate a high- or low- stress condition. Milk and saliva samples were collected during the treatment period to investigate the effect of maternal stress on sow CORT and OXT concentrations. In addition, behavioral data and saliva samples for CORT analyses were collected from sows during a 4-h maternal separation (MS) followed by a reunion, and during a matched control day. During the MS, plasma samples were collected from piglets for CORT and OXT analyses. Behavioral data were also collected at regular intervals from a subset of these piglets. Results indicate significant increases in CORT concentrations in saliva and milk of ACTH sows during the lactational period. The ACTH and C sows did not differ behaviorally during separations or reunions, although there was a tendency for ACTH sows to lay less on their sides during control days. There were no significant effects of the piglet rearing condition on piglet activity or hormones. However, during reunions, control piglets had a stronger preference for contact with the sow than with other piglets compared to the mother-treated piglets. Piglets who were group-housed during separations also had lower CORT concentrations compared to single-housed piglets. Even though ACTH sows exhibited few behavioral indications of heightened stress responses, physiological changes in milk could have long-term implications for piglets. •There were few effects of maternal stress on sow behaviors.•Lactational stress resulted in increased cortisol in sow milk and saliva.•Physiological changes indicate a mode of potential stress transmission to offspring.•Piglet rearing condition influenced piglet social preferences.•Social support during maternal separations reduced stress responses in piglets.